CONCRETE, REINFORCED BY CARBON FIBRE COMPOSITE STRUCTURE, LOAD BEARING CAPACITY DURING CRACKING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Different authors conducted studies on fiber reinforced concretes (FRC) with carbon fibres of different lengths and some results showed that concrete mix with homogeneously distributed short fibres in their volume have good strength and ultra-strain compared to normal plain concrete mix. However, this study is focused more on 3-dimensional (3D) carbon fibre reinforced plastic (epoxy) CFRP composite thin rods frame used as a reinforcement in concrete which shows good increase in loadbearing and ductility. Were investigated concrete mixes with superplasticizer, nano-silica, quartz sand, fine natural sand and gravels. Diagonal cross bracing carbon fibre epoxy frames were used as a reinforcement giving better ductility results. Proposed study approach is to show that the reinforced concrete with provided materials have an increased performance in terms of ductility, sustainability, and load bearing in cracked statement. Total, four groups of concrete and each group with three beams were casted and tested in this experiment, three groups with three different shapes of carbon frames and three beams without frames to compare the mechanical properties after 28 days. Failure mechanisms in any particular case were analysed.